Association between the use of Proton Pump Inhibitors and Histamine-2 Receptor Antagonists and the risk of gastric cancer in Norway - Tran, Kenny Khang (UiT Norges arktiske universitet, 2021)
Background: The use of proton pump inhibitors (PPIs) on prescription has increased over the last decade in Norway. PPIs are an important medication in the treatment of acid related disorders such as peptic ulcer disease, gastroesophageal reflux disease and Helicobacter Pylori (H. Pylori) infection. However, many previous studies have raised concern about the potential risk of gastric cancer following the use of PPIs. In this registry-based study we will investigate the association between use of PPI and Histamine-2 receptor antagonist (H2RA) and the risk of gastric cancer in Norway. Methods: This population-based nested case-control study comprises all primary gastric cancer cases in Norway diagnosed between 2007 and 2015 at an age of 18-85 and registered in the Cancer Registry of Norway. Ten cancer free controls were matched to each case on birth year, sex and index date (date of diagnosis). PPI and H2RA drug exposure were retrieved from the Norwegian Prescription Database and modelled as binary use, long-term use, cumulative use and in an active comparator design. Moreover, we used a stratified cox regression adjusted for H. Pylori, residency, education, comorbidity and other drug use to assess the link between PPI and H2RA use and the risk of gastric cancer. Results: Among 33 847 individuals in this study, we found an increased risk of gastric cancer among PPI users (HR=1.25, 95% Cl 1.13-1.37) and long-term PPI users (HR=1.18, 95% Cl 1.03-1.36) in Norway. There was also a significant impact on gastric cancer among PPI users living in Northern Norway (HR=1.43, 95% Cl 1.27-1.61). However, the dose-response relationship for PPI and the corresponding results for H2RA were not associated with an increased risk of gastric cancer. Conclusion: The association found between PPI use and the increased risk of gastric cancer was most likely due to confounding by indication like H. Pylori infection and other unobserved confounders. Observational studies adjusted for all relevant confounders and larger clinical studies ...